Determining Factors Affecting Independent Auditing in Small, Medium and Big-sized Auditing Companies- Case in Vietnam - DR, HOANG THANH HANH . (The journal of contemporary issues in business and government, 2021)
Along with the development of the economy, auditing also gradually expands the subjects of their specific interest. Previous traditional objects such as financial statements have not necessarily lost their role and position, but cannot meet all the expectations and concerns of managers and investors about the situation of the enterprise. Understanding the picture of determining the factors affecting audit fees such as finding a composite array helps to evaluate an aspect of prices and reasonable fees of auditing firms to gradually improve the audit system. math in Vietnam. And in the current period, when the audit fees are more inadequate, reflecting the inadequacies of the unfair competition, not ensuring the quality of the audit report, the research and research of it more than ever. should be very important. By using the following main research methods: Document analysis, systematic analysis, comparative comparison, survey survey method and data analysis method, to measure impacts of some factors on auditing fee, we find out the technical projects with a large scale and the legal environment has a strong impact on the strategy and policy of the audit service market more. Last but not least, Evaluating the impact on audit fees also contributes to helping businesses make long-term as well as short-term development strategies that are suitable for their businesses.